A study of the structural and magnetic properties of nitrides of iron and nickel (XN; X = Fe, Ni) using density functional theory approach. (8th December 2020) - Atsue, T; Ogunniranye, I B; Oyewande, O E
Abstract: Transition metal nitrides possess important properties of interest such as superconductivity, high hardness, optical, electronic and magnetic among others which are relevant for technological applications. In this study, structural and magnetic properties of nitrides of iron and nickel have been investigated using generalized gradient approximation of Perdew–Burke–Ernzerhof revised for solids (GGA-PBEsol) as implemented in Quantum Espresso, a density functional theory based computational software package. The compounds were considered in the zinc blende face centered cubic (FCC), hexagonal closed packed (HCP) and primitive tetragonal structures and the results revealed that FeN and NiN energetically prefer zinc blende FCC structure. The results of spin polarized calculation indicated that FeN exhibited non-magnetic properties only in the zinc blende FCC structure and a magnetic moment of 2.17 μ B and 3.18 μ B per formula units in the HCP and primitive tetragonal structures respectively, whereas NiN was non-magnetic for the three crystal structures.